Comparative outcomes of open mesenteric bypass after a failed endovascular or open mesenteric revascularization for chronic mesenteric ischemia - Jacobs, Christopher R.; Scali, Salvatore T.; Jacobs, Benjamin N.; Filiberto, Amanda C.; Anderson, Erik M.; Fazzone, Brian; Back, Martin R.; Upchurch, Gilbert R.; Giles, Kristina A.; Huber, Thomas S. (Journal of vascular surgery, 2024)
Clinical practice guidelines have recommended an endovascular-first approach (ENDO) for the management of patients with chronic mesenteric ischemia (CMI), whereas an open mesenteric bypass (OMB) is proposed for subjects deemed to be poor ENDO candidates. However, the impact of a previous failed endovascular or open mesenteric reconstruction on a subsequent OMB is unknown. Accordingly, this study was designed to examine the results of a remedial OMB (R-OMB) after a failed ENDO or a primary OMB (P-OMB) for patients with recurrent CMI. All patients who underwent an OMB from 2002 to 2022 at the University of Florida were reviewed. Outcomes after an R-OMB (ie, history of a failed ENDO or P-OMB) and P-OMB were compared. The primary end point was 30-day mortality, whereas secondary outcomes included complications, reintervention, and survival. The Kaplan-Meier methodology was used to estimate freedom from reintervention and all-cause mortality, whereas multivariable Cox proportional hazards modeling identified predictors of death. A total of 145 OMB procedures (R-OMB, n = 48 [33%]; P-OMB, n = 97 [67%]) were analyzed. A majority of R-OMB operations were performed for a failed stent (prior ENDO, n = 39 [81%]; prior OMB, n = 9 [19%]). R-OMB patients were generally younger (66 ± 9 years vs P-OMB, 69 ± 11 years; P = .09) and had lower incidence of smoking exposure (29% vs P-OMB, 48%; P = .07); however, there were no other differences in demographics or comorbidities. R-OMB was associated with less intraoperative transfusion (0.6 units vs P-OMB, 1.4 units; P = .01), but there were no differences in conduit choice or bypass configuration.The overall 30-day mortality and complication rates were 7% (n = 10/145) and 53% (n = 77/145), respectively, with no difference between the groups. Notably, R-OMB had decreased cardiac (6% vs P-OMB, 21%; P < .01) and bleeding complication rates (2% vs P-OMB, 15%; P = .01). The freedom from reintervention (1 and 5 years: R-OMB: 95% ± 4%, 83% ± 9% vs P-OMB: 97% ± 2%, 93% ± 5%, respectively; log-rank P = .21) and survival (1 and 5 years: R-OMB: 82% ± 6%, 68% ± 9% vs P-OMB: 84% ± 4%, 66% ± 7%; P = .91) were similar. Independent predictors of all-cause mortality included new postoperative hemodialysis requirement (hazard ratio [HR], 7.4, 95% confidence interval [CI], 3.1-17.3; P < .001), pulmonary (HR, 2.7, 95% CI, 1.4-5.3; P = .004) and cardiac (HR, 2.4, 95% CI, 1.1-5.1; P = .04) complications, and female sex (HR, 2.1, 95% CI, 1.03-4.8; P = .04). Notably, R-OMB was not a predictor of death. The perioperative and longer-term outcomes for a remedial OMB after a failed intraluminal stent or previous open bypass appear to be comparable to a P-OMB. These findings support the recently updated clinical practice guideline recommendations for an endovascular-first approach to treating recurrent CMI due to the significant perioperative complication risk of OMB. However, among the subset of patients deemed ineligible for endoluminal reconstruction after failed mesenteric revascularization, R-OMB results appear to be acceptable and highlight the utility of this strategy in selected patients.